THE ANALYSIS OF CHINA UNIQUE SMALL TOWN POLICY FROM THE PERSPECTIVE OF ECOLINGUISTICS - Ma, Jing; Wen, Haili (Chinese Journal of Social Science and Management, 2023)
China’s government has attempted to take a unique path compared to other countries all over the world in the domains of urbanization and rural development. Unique Towns is one of the important institutional forms of entrepreneurship of this type. Unique Towns is a term initially put forward by a Chinese institutional entrepreneur in the document Notice on Developing Unique Towns, which was jointly issued by Ministry of Housing and Urban-Rural Development of the People’s Republic of China, China National Development and Reform Commission and China Ministry of Finance (2016), in a plan to build approximately 1,000 unique towns in China. According to the Chinese government’s documents, Unique Town is a new concept that is completely diﬀerent from the traditional idea of a town as an administrative unit, which is also not an industrial park but rather an innovation and entrepreneurship platform in the sense that it can integrate industrial production, residents’ daily life, and ecological space as three elements in a harmonious way. This article revealed the gap between the logic preset by the Chinese government and the logic received through public cognition by deploying Ecolinguistics discourse analytical methods of Salience and Erasure, etc. under the basis of examining the promotional corpus of the frst batch 127 China Unique Towns publishing by China Science and Technology Development Center with AntConc 3.2.0 as an auxiliary tool. In public social discourse represented by the promotion materials of the 127 Unique Towns, there is a keynote narration of tourism, which establishes a tourism-oriented story structure in the public’s mind. There is an obvious institutional logic shift from community logic to market logic in the process of Unique Town’s institutional entrepreneurship in China, which might be one of the important reasons for the failure of institutional entrepreneurship. According to the related theories in Ecolinguistics, language inﬂuences how we think about the world, and how we think inﬂuences how we act. Narrative economics believes that a wide range of discourses in the public language system can inﬂuence public ideas, and the spread of popular stories that could change through time can aﬀect economic outcomes. This article aimed to illustrate how discourse inﬂuences human behavior through analyses of a range of texts regarding China’s Unique Town. The goal of the analysis was to reveal the underlying stories people live by in the process of China Unique Town’s institutional entrepreneurship. This study suggests that changing the narrative modes of the public discourse system to construct more reasonable speech frame models could improve the eﬀect of institutional entrepreneurship of China’s Unique Towns at the top level.